Dynamics of Coupled Structures, Volume 4 Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 - Allen, Matthew S.; Mayes, Randall L.; Rixen, Daniel Jean.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Dynamics of Coupled Structures, Volume 4: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the fourth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of the Dynamics of Coupled Structures, including papers on: Experimental Nonlinear Dynamics Joints, Friction & Damping Nonlinear Substructuring Transfer Path Analysis and Source Characterization Analytical Substructuring & Numerical Reduction Techniques Real Time Substructuring Assembling & Decoupling Substructures & Boundary Conditions.
Chapter1. Techniques for Verification of Structural Acoustic Models,- Chapter2. Substructuring of Viscoelastic Subcomponents with Interface Reduction -- Chapter3. Parameter Estimation of Joint Models Using Global Optimization -- Chapter4. Real Time Hybrid Simulation of an Unmanned Aerial Vehicle -- Chapter5. An Integration of Mixed Contact Formulation with Model-Reduction Techniques -- Chapter6. Identification Reassembly Uncertainties for a Basic Lap Joint -- Chapter7. Effect of Far-field Structure on Joint Properties -- Chapter8. Real-time Hybrid Model Testing of Moored Floating Structures Using Nonlinear Finite Element Simulations. Chapter9. DIC Measurement of the Kinematics of a Friction Damper for Turbine Applications -- Chapter10. A Simultaneous Iterative Scheme for the Craig-Bampton Reduction Based Substructuring -- Chapter11. Using Blocked Force Data for Vibro-Acoustic Prediction and Simulation -- Chapter12. CMS with Large Contact Patches -- Chapter13. In Situ Measurements of Contact Pressure for Jointed Interfaces During Dynamic Loading Experiments -- Chapter14. Dual Craig-Bampton Method with Reduction of Interface Coordinates -- Chapter15. Substructuring of a Nonlinear Beam Using a Modal Iwan Framework, Part I: Nonlinear Modal Model Identification -- Chapter16. Substructuring of a Nonlinear Beam Using a Modal Iwan Framework, Part II: Nonlinear Modal Substructuring -- Chapter17. Dynamic Decoupling of Nonlinear Systems -- Chapter18. Nonlinear Substructuring Using Fixed Interface Nonlinear Normal Modes -- Chapter19. Dynamic Substructuring of Geometrically Nonlinear Finite Element Models Using Residual Flexibility Modes -- Chapter20. Optimal Transformation of Frequency Response Functions on Interface Deformation Modes -- Chapter21. A Recursive Coupling-decoupling Approach to Improve Experimental Frequency Based Substructuring Results -- Chapter22. Experimental Assessment of the Influence of Interface Geometries on Structural Dynamic Response -- Chapter23. Nonlinear Finite Element Model Updating, Part I: Experimental Techniques and Nonlinear Modal Model Parameter Extraction -- Chapter24. A Simpler Formulation for Effective Mass Calculated from Experimental Free Mode Shapes of a Test Article on a Fixture -- Chapter25. Nonlinear Finite Element Model Updating, Part II: Implementation and Simulation -- Chapter26. A Benchmark Structure for Validation of Experimental Substructuring, Transfer Path Analysis and Source Characterisation Techniques -- Chapter27. Nonlinear Modal Substructuring of Panel and Stiffener Assemblies via Characteristic Constraint Modes -- Chapter28. Experimental Evaluation of Multi-functional Nonlinear Floor Isolation Systems -- Chapter29. Variability of Dynamic Response in Jointed Structures -- Chapter30. Predicting the Dynamics of Flexible Space Payloads Under Different Boundary Conditions Through Substructure Decoupling -- Chapter31. Evolutionary Identification of Block-Structured Systems -- Chapter32. Modal Analysis of Transmission Line Cables.
Keywords: Mechanics, Applied; Solids; Buildings -- Design and construction; Multibody systems; Vibration; Solid Mechanics; Building Construction and Design; Multibody Systems and Mechanical Vibrations